(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Textiles are a major contribution to India’s exports, accounting for around 11 percent ofoverall exports, according to the latest estimate from IBEF and another report from ICRA. One of thegreatest employers and one of the most labour-intensive industries is textiles.For the present researchthe researcher has adopted a combination of both qualitative and quantitative data collection methods.Under qualitative approach a detailed review of literature is performed to understand the concept andproblem statement. The main objective of the study is to find out the relationship between leverage andprofitability of selected textile industry.